Internationalizing the history of psychology - Brock, Adrian C. (New York University Press ; Combined Academic [distributor], 2009)
While the United States was dominant in the development of psychology for much of the twentieth century, other countries have experienced significant growth in this area since the end of World War II. The percentage of those in the discipline who live and work in the United States has been growing smaller, and it is now impossible to completely understand the field if developments in psychology outside of the United States are ignored. Internationalizing the History of Psychology brings together luminaries in the field from around the world to address the internationalizing of psychology, each.